Extração de vias combinando métodos de detecção de regiões e linhas em imagens de intensidade de pulso laser - Mendes, Tatiana Sussel Gonçalves [UNESP]; Dal Poz, Aluir Porfírio [UNESP] (My University, 2011)
This paper aims at extracting street centerlines from previously isolated street regions by using the image of laser scanning intensity. In this image, streets are easily identified, since they manifest as dark, elongate ribbons contrasting with background objects. The intensity image is segmented by using the region growing technique, which generates regions representing the streets. From these regions, the street centerlines are extracted in two manners. The first one is through the Steger lines detection method combined with a line length thresholding by which lines being shorter than a minimum length are removed. The other manner is by combining the skeletonization method of regions based on the Medial Axis Transform and with a pruning process to eliminate as much as possible the ramifications. Experiments showed that the Steger-based method provided results better than the method based on skeletonization.
Treet extraction combining methods for region and line detection from laser scanning intensity images
Keywords: Detection of lines; Segmentation; Skeletonization; Street extraction